2016
DOI: 10.1371/journal.pone.0151249
|View full text |Cite
|
Sign up to set email alerts
|

Daily Activity and Nest Occupation Patterns of Fox Squirrels (Sciurus niger) throughout the Year

Abstract: The authors investigated the general activity and nest occupation patterns of fox squirrels in a natural setting using temperature-sensitive data loggers that measure activity as changes in the microenvironment of the animal. Data were obtained from 25 distinct preparations, upon 14 unique squirrels, totaling 1385 recording days. The animals were clearly diurnal, with a predominantly unimodal activity pattern, although individual squirrels occasionally exhibited bimodal patterns, particularly in the spring and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…The monitoring of collar temperature (T c ) is particularly suited to provide an index of location (in-nest vs. out-of-nest), as the temperature of the collar quickly rises to core temperature levels after the animals enter their thermally insulated nests and drops rapidly when the animals leave their nests (Lamb, 1995;Kanda et al, 2005;Lazerte and Kramer, 2011;Murray and Smith, 2012;Wassmer and Refinetti, 2016). These assumptions were confirmed by aligning T c -records with behavioral logs (Wassmer and Refinetti, 2016) including nest entries. A recent study using a very similar setup with a large population of North American red squirrels (Tamiasciurus hudsonicus) confirmed the paradigm with about 700 observations of nest exits and entries (Studd et al, 2016).…”
Section: Data Collectionmentioning
confidence: 94%
See 2 more Smart Citations
“…The monitoring of collar temperature (T c ) is particularly suited to provide an index of location (in-nest vs. out-of-nest), as the temperature of the collar quickly rises to core temperature levels after the animals enter their thermally insulated nests and drops rapidly when the animals leave their nests (Lamb, 1995;Kanda et al, 2005;Lazerte and Kramer, 2011;Murray and Smith, 2012;Wassmer and Refinetti, 2016). These assumptions were confirmed by aligning T c -records with behavioral logs (Wassmer and Refinetti, 2016) including nest entries. A recent study using a very similar setup with a large population of North American red squirrels (Tamiasciurus hudsonicus) confirmed the paradigm with about 700 observations of nest exits and entries (Studd et al, 2016).…”
Section: Data Collectionmentioning
confidence: 94%
“…Research on both aspects of activity is therefore essential to understand the biology of animal species. Locomotor activity has been shown to follow a reproducible daily pattern in numerous animal species, including tree squirrels (Tester, 1978;Adams, 1984;Koprowski and Corse, 2005;Wassmer and Refinetti, 2016). More than half a century ago, Aschoff (1966) observed that many, if not most, studies of locomotor activity had evinced a bimodal pattern with increased activity at dawn and dusk rather than a consolidated bout during the day or a consolidated bout during the night.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When attached externally to an animal, the temperature recorded is often intermediate between body temperature and the ambient temperature of the environment immediately surrounding the individual (Osgodd & Weigl, 1972;Studd, Boutin, McAdam, & Humphries, 2016;Tremblay, Cherel, Oremus, Tveraa, & Chastel, 2003). Most pertinent here, collar temperature likely offers useful information about behavioral state, as it tends to more closely approximate the body temperature of inactive animals confined in small spaces (e.g., thermal refuges) and to more closely approximate the air temperature experienced by active animals fully exposed to ambient conditions (Körtner & Geiser, 2000;Messier, Taylor, & Ramsay, 1994;Murray & Smith, 2012;Olson et al, 2017;Wassmer & Refinetti, 2016). However, depending on the ecology of the species and which of these two temperatures vary more, collar temperature can be used to monitor thermal exposure (Osgodd & Weigl, 1972;Kanda, Fuller, & Friedland, 2009) or heterothermic fluctuations indicative of torpor expression or hibernation (Lazerte & Kramer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, depending on the ecology of the species and which of these two temperatures vary more, collar temperature can be used to monitor thermal exposure (Osgodd & Weigl, 1972;Kanda, Fuller, & Friedland, 2009) or heterothermic fluctuations indicative of torpor expression or hibernation (Lazerte & Kramer, 2016). Most pertinent here, collar temperature likely offers useful information about behavioral state, as it tends to more closely approximate the body temperature of inactive animals confined in small spaces (e.g., thermal refuges) and to more closely approximate the air temperature experienced by active animals fully exposed to ambient conditions (Körtner & Geiser, 2000;Messier, Taylor, & Ramsay, 1994;Murray & Smith, 2012;Olson et al, 2017;Wassmer & Refinetti, 2016).…”
Section: Introductionmentioning
confidence: 99%